2005
DOI: 10.1158/0008-5472.can-04-3065
|View full text |Cite
|
Sign up to set email alerts
|

The Seco-Taxane IDN5390 Is Able to Target Class III β-Tubulin and to Overcome Paclitaxel Resistance

Abstract: A prominent mechanism of drug resistance to taxanes is the overexpression of class III B-tubulin. The seco-taxane IDN5390 was chosen for its selective activity in paclitaxel-resistant cells with an overexpression of class III B-tubulin. Moreover, the combined treatment paclitaxel/IDN5390 yielded a strong synergism, which was also evident in cell-free tubulin polymerization assays. In the presence of an anti-class III Btubulin as a blocking antibody, tubulin polymerization induced by paclitaxel and IDN5390 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 26 publications
2
53
1
Order By: Relevance
“…It has been reported that selective in vitro pressure by antitubulin agents is able to force tumor cells to develop drug resistance by overexpressing h III tubulin isotype (10,12,32). Conversely, we observed a decrease in the percentage of h III tubulin positivity in posttreatment tissue samples regardless of response to chemotherapy.…”
Section: Discussioncontrasting
confidence: 61%
“…It has been reported that selective in vitro pressure by antitubulin agents is able to force tumor cells to develop drug resistance by overexpressing h III tubulin isotype (10,12,32). Conversely, we observed a decrease in the percentage of h III tubulin positivity in posttreatment tissue samples regardless of response to chemotherapy.…”
Section: Discussioncontrasting
confidence: 61%
“…Orobol suppressed all isotypes of ß-tubulin with the strongest effect on ß4a and caused the structural changes in microtubles resulting in increased levels of apoptosis although the rate of apoptotic cells did not correspond well to the level of the orobolsensitization effect. While ß3 tubulin overexpression is highlighted in PX-resistant cells in some studies (25)(26)(27), the lower level of ß1, ß3 and ß4a in PX-sensitive cells is consistent with the data of Kavallaris et al (12) and Shalli et al (28). They documented that PX-resistant cells displayed a significant increase in ß1, ß3, and ß4a isotypes.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, TUBB3 appears an attractive target and TUBB3 targeting agents could improve our therapeutic arsenal against drug resistance. A first example of this is represented by the seco-taxane IDN5390, a compound able to selectively target TUBB3 (9). This drug exhibits unique properties of cytotoxic, antiangiogenic agent and inhibitor of cell motility (10) and is currently undergoing preclinical development.…”
Section: Introductionmentioning
confidence: 99%